EVOLUSI FASADE ADAPTIF RUMAH MODULAR - Basuki,; Ary Sismiani,; Johanes Bonivasius Muda, (ReTII, 2024)
Technological developments often affect the way residential buildings adapt to the environment. This is reflected in the appearance of building facades. This article presents a comparison of the development of modular houses in adapting to the environment along with technological developments. The focus of the study is more on the appearance of building facades. The analysis was carried out using a qualitative descriptive approach. The focus of the study is: (1) the development of modular houses before the industrialization era, (2) the development of modular houses before the mass industry era, (3) the development of modular houses in the digital technology era. Data collection was obtained from secondary data in the form of articles, books, seminar papers. Case studies through several case samples (case multiple) to provide examples of practice. The results of the study found that adaptive modular houses have been developed both in traditional architecture, mass industry era architecture, and the digital technology era. Traditional architectural modular houses in adapting to the environment are more static. Digital technology provides opportunities for the development of modular houses and their elements that are more dynamic (flexible), complex and integrated.